2001
DOI: 10.1269/jrr.42.255
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Malformation upon Gestational Age and Exposed Dose of Gamma Radiation

Abstract: In order to evaluate the importance of gestational age and the dose-incidence relationship by gamma radiation, pregnant ICR mice at gestational days from 2.5 to 15.5 days post-coitus (p.c.) were exposed to a single dose of 2.0 Gy and also at day 11.5 after conception, which was the most sensitive stage for the induction of major congenital malformations. The animals were sacrificed on day 18 of gestation and the fetuses were examined for mortality, growth retardation, changes in head size and other morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
5
6
0
Order By: Relevance
“…Our findings do support the study by S.H. Kim et al, who observed an elevated number of resorptions in the E7.5 group after exposure to gamma rays (2 Gy) in ICR mice (Kim et al, ). Dose‐dependent fetal weight loss at E18 was reported by Di Majo as well, following exposure to X‐irradiation (0.0–2.0 Gy) at the neurulation stage (E7.5), thus supporting our data (Di Majo et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings do support the study by S.H. Kim et al, who observed an elevated number of resorptions in the E7.5 group after exposure to gamma rays (2 Gy) in ICR mice (Kim et al, ). Dose‐dependent fetal weight loss at E18 was reported by Di Majo as well, following exposure to X‐irradiation (0.0–2.0 Gy) at the neurulation stage (E7.5), thus supporting our data (Di Majo et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Kim et al reported that high dose (2.0 Gy, 10 Gy/min) gamma irradiation of pregnant ICR mice during discrete stages of development induced the highest incidence of gastroschisis after irradiation at E7.5 (2.22%), which is in accordance with our results obtained with X‐rays. Interestingly, in their study the most radiosensitive stage for developing cleft palate was identified as E11.5 (36.59%), whereas we observed the highest incidence at E7.5 (Kim et al, ). Continuing, in swiss albino mice irradiated with 0.5 Gy Gamma rays, open eye defects were also found to be significantly more prevalent after irradiation at E17, suggesting that the induction of both cleft palate and open eye defects is not limited to irradiation during neurulation (Hossain, Devi, & Bisht, ).…”
Section: Discussionmentioning
confidence: 47%
“…Regulation of the embryonic cell cycle as influenced by induced damage is one aspect of translating the rates of CA, as observed in our study, with the developmental profiles in vivo, as for instance observed by Kim et al [4] and indicated before Heyer et al [3]. ES cells do not show a G1-S checkpoint, yet are sensitive to apoptosis (see in [46]).…”
Section: Cell Cycle Regulationsupporting
confidence: 85%
“…These authors showed this process to be ATM-and p53-dependent, demonstrating cell cycle checkpoints to be active. In line with this sensitivity for DNA damage-induced apoptosis, Kim et al [4] found that when determining prenatal death from 2 Gy gamma irradiation at prenatal days 2.5, 5.5, 7.5, 11.5 and 15.5, greatest sensitivity was observed at the morula stage, followed by gastrulation at day 7.5 (resp. 66% and 45% death).…”
Section: Introductionmentioning
confidence: 82%
“…Many other investigators have confirmed these findings, including Kim et al (2001), indicating no increase in malformations or growth retardation in mice following 2 Gy (gamma rays) at a preimplantation stage. Mole (1993) concluded that the preimplantation period is not a stage where an increase in viable malformations will result from irradiation.…”
Section: The All-or-none Phenomenonmentioning
confidence: 69%